2013
DOI: 10.1002/2013jf002813
|View full text |Cite
|
Sign up to set email alerts
|

Piping coarse-grained sediment to a deep water fan through a shelf-edge delta bypass channel: Tank experiments

Abstract: [1] It is now generally accepted that deltas that prograde to the shelf edge are able to transport coarse sediment to deep water either with or without sea level changes. However, it is still unclear how feeder rivers behave differently in the shelf-edge delta case to rivers found in a delta that progrades over the shelf. A series of nine shelf-edge delta experiments are presented to investigate the lateral mobility of the feeder channel at the shelf edge and the associated deep water depositional system under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…First, enhanced differential sedimentation on the shelf (high A s ∕A b ) could have served as a metaphorical sieve of coarsegrained sediment because there was significant accommodation in the shelfal depositional environments (e.g., fluvial-deltaic systems), leaving predominantly relatively fine-grained strata to accumulate in the deep-water region, such as the mud-rich strata associated with steeply rising shelf-edge trajectories. Second, enhanced differential sedimentation on the basin-floor areas (low to negative A s ∕A b ) serves to pipe coarse-grained sediment directly to the basin floor (Kim et al, 2013), resulting in a coarse-grained submarine fan such as the Red River submarine fan in the downdip of flat to slightly falling shelf-edge trajectories (Tables 2, 4). Third, enhanced differential sedimentation on the shelf (high A s ∕A b ) increases the relief of the clinoforms (high R c ), thereby increasing the angle and instability of the shelf resulting in large-scale mud-rich masswasting processes and resultant large amounts of MTDs, which is evident in deep-water strata in front of steeply rising trajectories (Tables 2, 4).…”
Section: Shelf-edge Trajectories and Stratal Stacking Patterns As Relmentioning
confidence: 99%
“…First, enhanced differential sedimentation on the shelf (high A s ∕A b ) could have served as a metaphorical sieve of coarsegrained sediment because there was significant accommodation in the shelfal depositional environments (e.g., fluvial-deltaic systems), leaving predominantly relatively fine-grained strata to accumulate in the deep-water region, such as the mud-rich strata associated with steeply rising shelf-edge trajectories. Second, enhanced differential sedimentation on the basin-floor areas (low to negative A s ∕A b ) serves to pipe coarse-grained sediment directly to the basin floor (Kim et al, 2013), resulting in a coarse-grained submarine fan such as the Red River submarine fan in the downdip of flat to slightly falling shelf-edge trajectories (Tables 2, 4). Third, enhanced differential sedimentation on the shelf (high A s ∕A b ) increases the relief of the clinoforms (high R c ), thereby increasing the angle and instability of the shelf resulting in large-scale mud-rich masswasting processes and resultant large amounts of MTDs, which is evident in deep-water strata in front of steeply rising trajectories (Tables 2, 4).…”
Section: Shelf-edge Trajectories and Stratal Stacking Patterns As Relmentioning
confidence: 99%
“…To begin answering these two questions, we will relate the mid-Holocene to present geomorphic evolution of the LCR to the experimental results of Kim et al (2013) who investigated the morphodynamics of shelf-edge deltas. For clarity, we are not herein suggesting that the mid to late Holocene LCR system was/is a shelf-edge delta.…”
Section: Lcr Mid To Late Holocene Geomorphic/ Sedimentological Modelmentioning
confidence: 99%
“…Building on the results of Clarke et al (2010), the physical experiments of Kim et al (2013) employed a constant upstream sediment feed rate and steady base-level elevation, and found that under these steady boundary conditions deltas that prograde to a shelf-edge (where there exists a steep gradient in water depth/accommodation between the toe of the delta and the basin floor) cannot completely fill this space immediately via submarine fan sedimentation ( Fig. 6.5).…”
Section: Lcr Mid To Late Holocene Geomorphic/ Sedimentological Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researchers have argued conceptually (Burgess and Hovius 1998) and have demonstrated with ancient datasets that rising and high sea-level stand can also produce deepwater fans in high-sediment-supply basins Steel 2006, 2009;Covault et al 2007;Covault and Graham 2010;Kim et al 2013). The behavior and process regime of shelf-edge deltas (sediment feeder to deep water) in high-sediment-supply basins is also now known to impact the presence and volume of deep-water fans (Dixon et al 2012).…”
Section: Introductionmentioning
confidence: 99%